Alternate field evaporation by changing laser pulsing and voltage pulsing dynamically for atom probe analysis. (17th September 2018) - Taniguchi, M.; Nishikawa, O.
Abstract : Time‐of‐flight mass analysis in atom‐by‐atom scale is performed in atom probe (AP) by pulsed field evaporation of sample material. The pulsed field evaporation is triggered by superposing voltage pulse or shooting laser pulse together with stationary voltage for evaporation field. Voltage pulse which has been used from the establishment of AP in the 1960s is going to be replaced by short pulsed laser with high repetition rate in the nanometer scale characterization of materials by 3‐dimensional AP. The criterion for choosing appropriate trigger method is not clear because it is difficult to compare the result of 2 triggering method applied on the same sample in atomic scale. The precise comparison of 2 triggering method was enabled by applying voltage pulse and laser pulse alternately to the identical sample. The results of composition and spatial information reflected the mechanism of assisting field evaporation. But the evaporation order was almost random or disordered showing no correlation between 2 triggering method. To make clear the correlation between voltage pulsing and laser pulsing, the authors report their new system forcing alternate evaporation switching to the other trigger after the detection of ion in 1 trigger between voltage and laser.